Literature survey on the relationships between energy, environment and economic growth. (March 2017) - Tiba, Sofien; Omri, Anis
Abstract: The aim of this study is to exhibit an exhaustive survey which is related to the great flight of the literature of energy- environment-growth nexus at the individual and regional scale studies covering the period from 1978 to 2014. The survey takes into consideration the sample (country, region, etc.), periods covering, econometric strategies, and conclusions. Our survey is based on the causality direction among (i) the energy use variables (electricity, nuclear, renewable and non-renewable) and output growth; (ii) between economic growth and environment; and between the three variables at the same time. Globally, these surveys provide paradoxical and not conclusive results which energy consumption can boost economic growth through the productivity enhancement and it can boost also the environmental damages through the enhancement of pollutant emissions. Our survey sheds more the lights on the energy-environment-growth literature by giving an extensive listing (1978–2014) of these causal linkages among the energy use variables, environment and economic growth for both individual and collective cases. There is a unanimous consensus about the importance of dealing with such dynamic relationship, which is seems to be a cornerstone element in setting any ambition strategies (energy, ecological and economics).